049 Under PRESsure – an unusual trigger of posterior reversible encephalopathy. (23rd August 2021) - Thomas, James O; Williams, David B; Grainge, Christopher
Abstract : Background: A 68-year-old female, and experienced recreational diver, presented via a regional hospital to our neurology service with acute onset visual disturbance following a 30-metre open water dive. She had no significant past medical history, specifically no history of hypertension and was on no regular medications. She was an ex-smother with a 20 pack year history On arrival she was hypertensive to 190/100mmHg but otherwise systemically stable. She had intact visual acuity and visual fields but had difficulty distinguishing objects from complex backgrounds and described vivid visual distortions. MRI performed acutely demonstrated multifocal areas of T2 hyperintensity within her posterior parietal and occipital lobes and a provisional diagnosis of posterior reversible encephalopathy syndrome (PRES) was made. Further questioning revealed that the patient was diving with a 70/30% nitrogen/oxygen mixture for which she had not received appropriate training, and was diving at depths close to the recommended limits for this mixture. Diving mixtures containing higher concentrations of oxygen are used to reduce the risk of nitrogen narcosis and decompression sickness but can be associated with CNS toxicity thought to be due to significantly increased PaO2 and associated cerebral vasoconstriction. The patient was managed with intensive blood pressure control and made a significant recovery within seven days. Conclusions: We postulate that her PRES may have been triggered by excessive cerebral vasoconstriction from hyperoxaemia in a patient with impaired vasoregulatory reserve. References: Wingelaar TT, van Ooij P-JAM, van Hulst RA. Oxygen toxicity and special operations forces diving: hidden and dangerous. Front Psychol 2017;8 :1263. doi:10.3389/fpsyg.2017.01263 Matsuo R, Kamouchi M, Arakawa S, Furuta Y, Kanazawa Y, Kitazono T. Magnetic resonance imaging in breath-hold divers with cerebral decompression sickness. Case Rep Neurol 2014;6(1):23–27. Published 2014 Jan 24. doi:10.1159/000357169